Conference report: the importance of the gut microbiome and nutrition on health. (20th December 2021) - Ball, Derek; Athanasiadou, Spiridoula
ABSTRACT: The Nutrition Society Spring Conference (28–29 March 2021) focussed on the gut microbiome and health that was divided across three separate but inter-related areas from the impact of nutrition on the gut microbiome, the cause and effect of nutrition and health on the gut microbiome to the interaction between pathogens and gut microbiota. The program was supported by two plenary lectures, the first discussed the computational methods commonly employed to examine gut microbiota and the concluding lecture presented the interaction between gut microbiome, nutrition and health in older populations.